Post harvest changes of γ-irradiated banana ’Prata’ - Vilas Boas, Eduardo Valério de Barros; Chitarra, Adimilson Bosco; Chitarra, Maria Isabel Fernandes (Pesquisa Agropecuaria Brasileira, 1996)
The effect of the γ-irradiation was evaluated at 0.25 and 0.50 kGy, on the development of peel coloration, CO2 and ethylene evolution, conversion of starch to sugars, pulp-to-peel ratio, pectic solubilization and activities of enzymes of the cell wall, pectinmethylesterase (PME), and polygalacturonase (PG), during maturation of ’Prata’ bananas. The γ-irradiation did not affect the normal colour development of the fruits. An increase in the ethylene peak and a decrease in the CO2 peak was observed. The γ-irradiation did not affect the degradation of starch, while a delay in soluble sugar accumulation was noted on the 6 and 7 colour grades. The fruits subjected to 0.25 kGy had the highest increase in the pulp-to-peel relation, beginning with colour grade 5, due to a possible stress effect of that dose. An increase of pectin solubilization was observed. Higher PME activities were exhibited by irradiated fruits, although the γ-irradiation suppressed the PG activity throughout the maturation period. The γ-irradiation did not extend the post-harvest life of ’Prata’ bananas.